Factors related to productivity in the knotting process of Piña fibers - Basa, Crisanta Ingalla
Pina, a fabric of elegance, rarity, and beauty has always been admired throughout the world. The complex process involved in producing the pina cloth has been attributed to the artistic inguinity of the Filipino people. Among the problems mentioned in the 1996 Annual report of the Fiber Industry Development Authority (FIDA), were the unsteady supply of fibers and very few pina knotters and scrapers. As native of Aklan, the acknowledged center of pina fiber and cloth production in the country, the researcher deemed it important to gather more information on the factors related to productivity. The researcher noted that the fiber knotting process is a bottleneck in the pina cloth production. Unlike fiber extraction (scraping) and weaving, which been well-documented, very limited information is available on the knotting of pina fibers. The study concentrated on the details of the knotting process, output of knotters and factors related to productivity. Data were gathered from 22 pina fiber knotters from two towns in Aklan: Banga and Kalibo. Basic information regarding the industry were gathered through inerviews and reports of all identified government agencies. A time study of the knotting process was also conducted and interviews with the fiber knotters were also undertaken. Correlation of the different factors related to productivity were obtained using Statistical Analysis System (SAS), a software for the data analysis. For the time study, weighted average was used to achieve the standard time of the knotting process. The findings of the study were: a0 the knotting process was very simple, which consisted of eight elements and the standard time was 57.05 seconds. b) Most of the fiber knoters were housewives and were engaged in the process only during their free time. The output of the fiber knotter's per "bas-ing" (35 grams) compared to knotter's level of skill were: a slow knotter can finish a "bas-ing" in a month or more, output per day was 1.12 grams, while an average knotter can finish the same amount for three weeks to a month and output per day was 1.5 grams. However, a highly skilled knotter can finish a "bas-ing" in two weeks or less, and output per day was 2.2 grams. Of the 12 factors correlated with perceived productivity output, only six were found to be significant: age, working hours, years of experience, working environment (wind), eye strain and length of available fibers. The remaining six factors were found not significant to productivity: condition of "sag-uton" and the knotting process (fibers get easily entangled), tedious fiber preparation, brittleness of the fiber, and c). distance involved from source of for knotting. Based on the results of the study the following recommendations were made: a) government and private agencies must increase their share of financial support for the industry as a whole, and exert more efforts by conducting trainings to increase their share of financial support for the industry as a whole, and exert more efforts by conducting trainings to increase number of knotters and production of good quality, and long loose fibers for knotters, b). Department of Trade and Industry (DTI) should study the earnings of the weavers and scrapers compared to the knotter's earning per month, c). the people in the barangay should form cooperatives and associations to supply loose fibers to the knotters, and, d). test the form cooperatives and associations to supply loose fibers to the knotters, and, d). test the revised reeling/winding machine developed by the Philippine Textile Research Institute (PTRI), to facilitate fiber preparation for weaving.